Electrochemical CO2 Reduction: Electrochemical CO2 Reduction Using Electrons Generated from Photoelectrocatalytic Phenol Oxidation (Adv. Energy Mater. 18/2019). Issue 18 (9th May 2019) - Guo, Chenyan; He, Peng; Cui, Rongrong; Shen, Qi; Yang, Nianjun; Zhao, Guohua
Abstract : Nezha, a protection deity in Chinese folk religion, is known for combating demons. In article number1900364, Nianjun Yang, Guohua Zhao, and co‐workers report the utilization of electrons generated from photoelectrocatalytic pollutant oxidation for efficient CO2 reduction. The electrons transfer in the same way as Nezha flies from the sea to the sky along with a red silk.